Indonesia Islamic Financial Institution's Cost efficiency and Welfare Performance : Evidence from Economic's Recovering Country - Kuncoro Catur Nugroho; Zainul Wasik; MahjudinMahjudin; Dody Suhermawan (PT. Mawadaku Sukses Solusindo, 2023)
Purpose – The study examines the relationship between the consequential social cost of market power (i.e., welfare performance of banks) and cost efficiency using data covering the period 2009 to 2017 in both private own Islamic banks and state owned Islamic Banks in Indonesia. Design/methodology/approach – The study adopts the Ordinary Least Squares (OLS), Fixed Effect (FE) panel regression and the Quantile regression (QR) approaches to control for heterogeneity and provide increased room for policy relevance. The Two-Stage Least Squares Instrumental Variables (2SLS-IV) regression is used to ensure the robustness of the findings against the problem of possible reverse causality. Findings – The results indicate a positive relationship between banks’ welfare performance and cost efficiency, which suggests that greater cost efficiency hedges welfare losses. In other words, welfare gains and cost-efficient banks are not mutually exclusive. Also, the results show evidence that the sensitivity of welfare gain to cost efficiency depends on the knowledge of local market dynamics. Further, the findings from the QR estimation suggest that, but for welfare loss at low (Q.25) to the median (Q.50) quantiles, cost efficiency is a necessary and sufficient condition to hedge the welfare losses.